In-vitro evaluation of silage production using banana waste and sweet potato plant - Gultom, Roselin; Maria Nali, Anna; Jehanu, Angelus; Windiatma Gandi, Prisilia; Nelson Bernard, Severinus (Politeknik Negeri Jember, 2024)
Banana stems and peels (Musa paradisiaca. Val), and sweet potato plants (Ipomoea batatas) are agricultural waste that can be used as animal feed to be processed into silage through a fermentation process. This study was conducted to evaluate the physical and chemical quality of silage. The physical quality examination includes aroma, color, texture, and fungal contamination levels. In comparison, chemical quality measurements include pH value, dry matter content, and score fleigh (SF). The design of this study used a Completely Randomized Design with 4 treatments and 5 replications. The treatments include, P1: 100% banana stems; P2: 100% sweet potato; P3: 50% banana stems + 50% banana peel; and P4: 50% sweet potato + 50% banana peel. The results of this study did not have a significant effect (P>0.05) on the physical and chemical quality of silage. The physical quality of silage was identified as being paler in color than the original feed ingredients, had a sour aroma, and no fungi were detected. The physical quality of the silage from banana stems, sweet potato plants, a combination of banana stems and banana peels, and a combination of sweet potato plants and banana peels showed equally good quality. However, the chemical quality of the silage produced did not meet the standards of good silage in terms of dry matter content (28.74-29.1%), pH value (5.9-5.6), and score fleigh (26.48-39.2).